Dating the Passion : the Life of Jesus and the Emergence of Scientific Chronology (200-1600). - Nothaft, C. Philipp E. (Time, astronomy, and calendars ;, 2011)
Drawing on computistical and astronomical sources from late antiquity to the Renaissance, this book demonstrates how pre-modern Christian attempts to determine the principal dates of the life of Jesus played an essential role in the development of historical chronology.